Health Information Processing and Online Health Information Seeking Pathways in the New Media Environment: A Review Based on Shaohai Jiang's Research - Wu, Yumeng (The Journal of Medicine, Humanity and Media, 2026)
The advancement of internet technology has reshaped health communication, bringing new opportunities and challenges to academic exploration. Centering on "how new media technologies improve people's health," this study systematically synthesizes the academic achievements of Shaohai Jiang in health communication. This study found that at the health knowledge level, Jiang explores the dual influential mechanisms of digital technology on health communication based on theoretical frameworks such as the Cognitive Mediation Model (CMM) and the Three-Stage Model of Interactive Media Use for Health Promotion. Besides, at the health behavior level, Jiang conducts multi-dimensional and cross-contextual academic investigations into the antecedent mechanisms and behavioral effects of online health information seeking (IHIS). Additionally, Jiang examines the application value of new media in specialized areas including patient-centered communication (PCC) and older adults' e-health literacy. His research enriches the application boundaries of health communication theoretical models from a quantitative perspective, providing significant academic references for health communication practices in today’s new media environment.